Federal statehood of Russia and Germany in the mirror of constitutional and judicial law enforcement: the importance of German experience for Russian practice - Elena V. Gritsenko (Правоприменение, 2019)
The subject of the article is the application of the constitutional foundations of federalism by the constitutional courts of Germany and Russia. The contribution of the highest courts of Russia and Germany to the development of the constitutional concept of the Federal system through judicial interpretation of the basic principles of Federal statehood directly enshrined in the Constitution and the discovery of unwritten principles is studied.The purpose of the article is to confirm or disprove hypothesis that German federalism reflects mostly competition model with specific elements of cooperation of federative entities, while the Russian federalism demonstrates the increasing vertical cooperative principles.The methodology of the study includes analysis, synthesis, description as well as particular academic legal methods (comparative analysis of legislation and judicial decisions, formal‐legal method, interpretation of legal acts).The main results and scope of their application. Competitive and cooperative principles exist in any system of federal relations. Their ratio, as well as the actual status of the Federation and its constituent entities  reflect the features of a particular model of federal structure. Federal reform in Germany 2006-2009 was aimed to return competitive origins in the German federalism and was opposed to unitarist trends. The origins of significant differences in approaches to the interpretation of the nature of the Union state in Germany and the Federation in Russia are rooted in various historical and political prerequisites for the formation and development of both federal States as well as in national traditions. This is reflected in the varying degrees of doctrinal elaboration of the theory of the federal state in Russia and Germany. The unwritten principle of fidelity to Federal relations is very important for the understanding of the peculiarities of German federalism. It is based on the provisions of the Basic law and disclosed in the decisions of the Federal constitutional court. This principle presupposes a friendly attitude of the central state and the federal lands to each other and to the Federation, cooperation, mutual respect and mutual assistance. It seems that this principle can serve as a basis for the disclosure of relations between the constituent entities and central state in Russia. The functional model of the Federal organization is implemented in Germany, unlike Russia. First of all, the Basic Law for Germany focuses on the horizontal separation of powers and uses the functional principle of the separation of state powers between the Bund and the Federal lands making a distinction, respectively, primarily in the areas of legislation, execution of laws (management) and justice. The Russian concept of vertical separation of powers is characterized by a different approach: horizontal separation of powers does not precede vertical separation of powers. Competence between the Federation and it’s constituent entities is differentiated not by functional, but by subject matter (by subjects of competence).Federal constitutional courts play special role in the interpretation of the constitutional principles of the Federal system and their development. This is confirmed both by the practice of the Federal Constitutional Court of Germany (FCC) and by the decisions of the Russian Constitutional Court (CC RF). Revealing the nature of the German Union state on the basis of the interpretation of the provisions of the Basic Law, the FCC relies on the existing doctrine on this issue. The FCC's legal positions on federal relations are also important for Russian doctrine and practice. It concerns the principles of inviolability of the constitutional basis of federal statehood, fidelity to the Federation and friendly attitude to the principles of federal structure, including horizontal and vertical interaction in the system of federal relations, mutual assistance, mutual nature of the rights and obligations of the Federation and its constituent entities.Conclusions. Unlike Germany, the Russian federalism is increasingly strengthening vertical cooperative basics, which hides the model of a highly centralized Federation. This conclusion is confirmed by the non-recognition of their own source of statehood of the subjects of the Russian Federation, in fact, their lack of quality of constitutional autonomy.